α-type sialon phosphor, light-emitting device, and method for manufacturing α-type sialon phosphor
Patent Information
- Application Number
- KR1020257034323
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-03-31
- Filing Date
- 2024-03-22
- Publication Date
- 2026-09-22
- Estimated Expiration
- 2044-03-22
Smart Images

Figure 112025114965579-PCT00006_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to an α-type sialon phosphor, a light-emitting device, and a method for manufacturing an α-type sialon phosphor. Background Technology
[0002] α-type sialon phosphors, which are revitalized with rare earth elements such as Eu, are applied to wavelength conversion components of white LEDs because they can efficiently convert blue light into long-wavelength light.
[0003] α-type sialon phosphors typically have a structure in which the Si-N bonds of α-type silicon nitride crystals are partially replaced by Al-N and Al-O bonds, and specific elements (Ca, and lanthanide metals excluding Li, Mg, Y, or La and Ce) are interstitially dissolved within the crystal lattice to maintain electrical neutrality. Fluorescence properties are exhibited by making some of the interstitially dissolved elements rare earth elements that serve as emission centers. In particular, α-type sialon phosphors in which Ca is dissolved and a portion thereof is substituted with Eu are excited relatively efficiently over a wide wavelength range from ultraviolet to blue, exhibiting yellow or orange emission.
[0004] Various attempts have been proposed to further improve the fluorescence properties of α-type sialon phosphors (e.g., Patent Documents 1–3, etc.). Prior art literature
[0005] Patent Document 1: Japanese Published Patent Application No. 2009-96882 Patent Document 2: Japanese Patent Publication No. 6667025 Patent Document 3: Japanese Patent Publication No. 6785333 The problem to be solved
[0006] It is thought that a white LED using an α-type sialon phosphor as a wavelength conversion element can be applied to automotive applications.
[0007] For automotive applications, it is required that various characteristics of white LEDs not change even under high temperatures. However, as a result of the inventors' preliminary investigation, it became clear that white LEDs using a conventional α-type sialon phosphor as a wavelength conversion element exhibit significant changes in luminescence characteristics under high-temperature environments.
[0008] The present invention was made in consideration of such circumstances. One of the objectives of the present invention is to provide an α-type sialon phosphor that is difficult to change in luminescence characteristics even under high temperature environments when used as a wavelength conversion member of a white LED. means of solving the problem
[0009] The inventors have solved the above problem by completing the invention provided below.
[0010] 1.
[0011] As an α-type sialon phosphor containing the element Eu,
[0012] The density of crystal defects in the above α-type sialon phosphor is 1.0×10⁻⁶, as the spin density value of the signal near g=2 detected by electron spin resonance measurement at 25°C. 15 α-type sialon phosphor with spins / g or less.
[0013] 2.
[0014] As an α-type sialon phosphor containing the element Eu,
[0015] The density of crystal defects in the above α-type sialon phosphor is 1.0×10⁻⁶, as the spin density value of the signal near g=2 detected by electron spin resonance measurement at 200°C. 15 α-type sialon phosphor with spins / g or less.
[0016] 3.
[0017] As an α-type sialon phosphor described in 2,
[0018] The density of crystal defects in the above α-type sialon phosphor is 1.0×10⁻⁶, as the spin density value of the signal near g=2 detected by electron spin resonance measurement at 25°C. 15 α-type sialon phosphor with spins / g or less.
[0019] 4.
[0020] As an α-type sialon phosphor described in any one of 1 to 3,
[0021] The density of crystal defects in the above α-type sialon phosphor is 1.0×10⁻⁶, as the spin density value of the signal near g=2 detected by electron spin resonance measurement at 300°C. 15 α-type sialon phosphor with spins / g or less.
[0022] 5.
[0023] As an α-type sialon phosphor described in any one of 1 to 4,
[0024] The density of crystal defects in the above α-type sialon phosphor is 9.5×10⁻⁶, as the spin density value of the signal near g=2 detected by electron spin resonance measurement at 600°C. 15 α-type sialon phosphor with spins / g or less.
[0025] 6.
[0026] As an α-type sialon phosphor described in any one of 1 to 5,
[0027] α-type sialon phosphor having an internal quantum efficiency of 87% or higher at 200℃.
[0028] 7.
[0029] As an α-type sialon phosphor described in any one of 1 to 6,
[0030] α-type sialon phosphor having an internal quantum efficiency of 80% or more at 300℃.
[0031] 8.
[0032] As an α-type sialon phosphor described in any one of 1 to 7,
[0033] α-type sialon phosphor having an internal quantum efficiency retention rate of 89% or higher, represented by {(internal quantum efficiency at 24℃) / (internal quantum efficiency at 300℃)}×100[%].
[0034] 9.
[0035] As an α-type sialon phosphor described in any one of 1 to 8,
[0036] α-type sialon phosphor having an external quantum efficiency retention rate of 88% or higher, expressed as {(external quantum efficiency at 24℃) / (external quantum efficiency at 300℃)}×100[%].
[0037] 10.
[0038] As an α-type sialon phosphor described in any one of 1 to 9,
[0039] Composition, general formula: (M1 x , M2 y , Eu z )(Si 12-(m+n) Al m+n )(O n N 16-n It appears as ),
[0040] In the above general formula,
[0041] M1 is a monovalent Li element,
[0042] M2 is one or more divalent elements selected from the group consisting of Mg, Ca, and lanthanide elements (excluding La and Ce),
[0043] 0≤x<2.0, 0≤y<2.0, 0 <z≤0.5, 0<x+y, 0.3≤x+y+z≤2.0, 0<m≤4.0, 0<n≤3.0인 α형 사이알론 형광체.
[0044] 11.
[0045] A light-emitting element and,
[0046] A light-emitting device comprising an α-type sialon phosphor described in any one of 1 to 10, and a wavelength conversion unit that converts light emitted from the light-emitting element into a long wavelength.
[0047] 12.
[0048] A calcination process for obtaining a massive α-type sialon phosphor containing Eu elements by calcination, and
[0049] A grinding process for grinding the above-mentioned bulk α-type sialon phosphor to obtain a powdered α-type sialon phosphor, and
[0050] An N2 annealing process for annealing the powdered α-type sialon phosphor under a nitrogen gas atmosphere, in a temperature range of 1200°C to 1700°C and a time range of 5 hours to 30 hours, and
[0051] An H2 annealing process for annealing the powdered α-type sialon phosphor under a hydrogen gas atmosphere, in a temperature range of 1200°C or higher and 1700°C or lower and a time range of 5 hours or higher and 30 hours or lower, and
[0052] A method for manufacturing an α-type sialon phosphor comprising an acid treatment process in which an acid treatment is performed using an acidic aqueous solution on the powdered α-type sialon phosphor after the H2 annealing process. Effects of the invention
[0053] The white LED using the α-type sialon phosphor of the present invention as a wavelength conversion member is unlikely to have changes in light emission characteristics even under high temperature environments. Brief explanation of the drawing
[0054] Figure 1 is a schematic cross-sectional view showing an example of the structure of a light-emitting device. Specific details for implementing the invention
[0055] Hereinafter, embodiments of the present invention will be described in detail with reference to the drawings.
[0056] In drawings, the same reference numerals are assigned to identical components, and descriptions are omitted as appropriate.
[0057] In order to avoid clutter, if there are multiple identical components within the same drawing, only one is assigned a symbol, and none of them are assigned a symbol.
[0058] Drawings are for illustrative purposes only. The shapes and dimensional ratios of each component in the drawings do not necessarily correspond to actual products.
[0059] In the description of numerical ranges in this specification, the notation "X~Y" indicates X or more and Y or less, unless specifically explained otherwise. For example, "1~5 mass%" means "1 mass% or more and 5 mass% or less."
[0060] In this specification, "α-type sialon phosphor containing Eu element" may be simply referred to as "α-type sialon phosphor."
[0061] In this specification, "signal near g=2" means a signal in which the g value in the electron spin resonance measurement is near 2, as indicated by the literal meaning of the characters. Specifically, g=2 near means g=2±0.02.
[0062] α-type sialon fluorescence
[0063] The α-type sialon phosphor of the present embodiment contains the element Eu. In other words, the α-type sialon phosphor of the present embodiment is an Eu-reactivated α-type sialon phosphor.
[0064] The α-type sialon phosphor of this embodiment satisfies one or both of the following (1) and (2).
[0065] (1) The crystal defect density in the α-type sialon phosphor of the present embodiment is 1.0×10⁻⁶, which is the spin density value of the signal g=2 detected by electron spin resonance measurement at 25°C.15 It may be less than or equal to spins / g. This value is preferably 1.0 × 10⁻⁶. 14 spins / g or more 8.0×10 14 spins / g or less, more preferably 1.0×10 13 spins / g or more 6.0×10 14 It is less than spins / g.
[0066] (2) The crystal defect density in the α-type sialon phosphor of the present embodiment is 1.0×10⁻⁶, which is the spin density value of the signal g=2 detected by electron spin resonance measurement at 200°C. 15 It may be less than or equal to spins / g. This value is preferably 1.0 × 10⁻⁶. 14 spins / g or more 8.0×10 14 spins / g or less, more preferably 1.0×10 13 spins / g or more 6.0×10 14 It is less than spins / g.
[0067] The inventors examined the causes of changes in luminescence characteristics under high-temperature environments from various perspectives. Through this examination, the inventors hypothesized that the value of crystal defect density obtained through electron spin resonance (ESR) measurements might be correlated with the degree of change in luminescence characteristics. This is because the presence of crystal defects is generally thought to cause a degradation of luminescence characteristics.
[0068] Based on the above idea, the inventors newly fabricated an α-type sialon phosphor in which the density of crystal defects obtained through electron spin resonance (ESR) measurements at 25°C and / or 200°C is sufficiently small. By using this new α-type sialon phosphor as a wavelength conversion element for a white LED, it was possible to manufacture a white LED in which the luminescence characteristics are difficult to change even under high-temperature environments.
[0069] The fact that the density of crystal defects at 200°C is sufficiently small means that there are few crystal defects even under high-temperature environments. If the density of crystal defects under high-temperature environments is small, it is thought that various properties are difficult to change even under high temperatures during vehicle use, and therefore, luminescence properties are also difficult to change.
[0070] In addition, it is thought that if the density of crystal defects is sufficiently small even at 25°C rather than 200°C, the crystal defects tend to decrease in response even under high-temperature environments. That is, if the density of crystal defects is sufficiently small at 25°C, it is thought that the luminescence characteristics are unlikely to change even under high-temperature environments.
[0071] The α-type sialon phosphor of the present embodiment can be manufactured by undergoing an appropriate manufacturing process. Specifically, the α-type sialon phosphor of the present embodiment can be manufactured by performing two annealing processes: an N2 annealing process in which a powdered α-type sialon phosphor is annealed under a nitrogen gas atmosphere, and an H2 annealing process in which a powdered α-type sialon phosphor is annealed under a hydrogen gas atmosphere. If the manufacturing method is inappropriate, the α-type sialon phosphor of the present embodiment may not be obtained.
[0072] Details of the manufacturing method will be explained later.
[0073] The description of the α-type sialon phosphor of the present embodiment continues.
[0074] · Composition of the phosphor
[0075] The composition of the α-type sialon phosphor of the present embodiment is, for example,
[0076] General formula: (M1 x , M2 y , Eu z )(Si 12-(m+n) Al m+n )(O n N 16-n )
[0077] It can be represented as.
[0078] In the above general formula,
[0079] M1 is a monovalent Li element,
[0080] M2 is one or more divalent elements selected from the group consisting of Mg, Ca, and lanthanide elements (excluding La and Ce),
[0081] 0≤x<2.0, 0≤y<2.0, 0 <z≤0.5, 0<x+y, 0.3≤x+y+z≤2.0, 0<m≤4.0, 0<n≤3.0
[0082] am.
[0083] The solid solution composition of the α-type sialon phosphor is represented by m and n, which are determined by x, y, and z in the above general formula and the Si / Al ratio or O / N ratio associated therewith. In particular, when M2 contains Ca, the α-type sialon phosphor is stabilized over a wide compositional range, and by substituting a part of it with Eu, which becomes the emission center, it is excited by light in a wide wavelength range from ultraviolet to blue, and a phosphor is obtained that exhibits visible light emission from yellow to orange.
[0084] Generally, the solid solution composition of the α-type sialon phosphor cannot be strictly determined by compositional analysis, etc. due to a second crystalline phase different from the α-type sialon phosphor or an inevitably existing amorphous phase. As for the crystalline phase of the α-type sialon phosphor, the α-type sialon single phase is preferred, and other crystalline phases may include aluminum nitride or its polytyphoid, etc.
[0085] · Characteristics of the fluorescent material
[0086] α-type sialon phosphors are typically handled in the form of α-type sialon phosphor powder, which is a collection of α-type sialon phosphor particles.
[0087] α-type sialon phosphor particles often contain multiple primary particles that have become agglomerated secondary particles.
[0088] Median diameter (D) of α-type sialon phosphor powder 50 The lower limit of ) is preferably 1 μm or more, more preferably 5 μm or more, and more preferably 10 μm or more. In addition, the upper limit of the median diameter of the α-type sialon phosphor powder is preferably 30 μm or less, and more preferably 20 μm or less. The median diameter of the α-type sialon phosphor powder is the dimension in the above secondary particle. That is, D 50 The median diameter is preferably 1 μm or more and 30 μm or less, more preferably 5 μm or more and 30 μm or less, and even more preferably 10 μm or more and 20 μm or less. By making the median diameter of the α-type sialon phosphor powder 5 μm or more, the transparency of the wavelength conversion member can be further increased. Meanwhile, by making the median diameter of the α-type sialon phosphor powder 30 μm or less, chipping can be suppressed when the wavelength conversion member is cut and processed with a die cutter or the like.
[0089] Here, the median diameter (D) of the α-type sialon phosphor powder 50 ) refers to the median diameter in the volume-based integrated fraction by the laser diffraction scattering method in accordance with JIS R1629:1997. For reference, if the α-type sialon phosphor powder contains secondary particles, the median diameter obtained by the laser diffraction scattering method reflects the size of the secondary particles.
[0090] The shape of the α-type sialon phosphor particles is not particularly limited. Examples of shapes include spherical, cubic, columnar, and irregular shapes.
[0091] · All characteristics under various temperatures
[0092] In addition to the crystal defect density (spin density) at 25°C and 200°C described above, by designing an α-type sialon phosphor to satisfy one or more of the characteristics described below, the performance of the α-type sialon phosphor can be further enhanced, especially at high temperatures.
[0093] The crystal defect density in the α-type sialon phosphor of the present embodiment is, preferably 1.0 × 10⁻⁶, the spin density of the signal near g=2 detected by electron spin resonance measurement at 300°C. 15 spins / g or less, more preferably 1.0×10 14 spins / g or greater than 1.0×10 15 spins / g or less, more preferably 4.0×10 14 spins / g or greater than 9.0×10 14 It is less than spins / g.
[0094] The crystal defect density in the α-type sialon phosphor of the present embodiment is, as the spin density value of the signal near g=2 detected by electron spin resonance measurement at 600°C, preferably 9.5×10⁻⁶ 15 spins / g or less, more preferably 5.0×10 15 spins / g greater than 9.5×10 15 spins / g or less, more preferably 7.5×10 15 spins / g greater than 9.5×10 15 It is less than spins / g.
[0095] The internal quantum efficiency of the α-type sialon phosphor of the present embodiment at 200°C is preferably 87% or higher, more preferably 88% or higher. It is preferable for this value to be as close to 100% as possible, but in reality, it is 95% or lower or 93% or lower. That is, the internal quantum efficiency at 200°C is preferably 87% or higher and 95% or lower, more preferably 88% or higher and 93% or lower.
[0096] The external quantum efficiency of the α-type sialon phosphor of the present embodiment at 300°C is preferably 80% or more, more preferably 82% or more. It is preferable for this value to be as close to 100% as possible, but in reality, it is 90% or less or 88% or less. That is, the external quantum efficiency at 200°C is preferably 80% or more and 90% or less, more preferably 82% or more and 88% or less.
[0097] In the α-type sialon phosphor of the present embodiment, the internal quantum efficiency retention rate, represented by {(internal quantum efficiency at 24°C) / (internal quantum efficiency at 300°C)}×100[%], is preferably 89% or more, more preferably 89% or more and 99% or less, and even more preferably 90% or more and 99% or less.
[0098] In the α-type sialon phosphor of the present embodiment, the external quantum efficiency retention rate, represented by {(external quantum efficiency at 24°C) / (external quantum efficiency at 300°C)}×100[%], is preferably 88% or more, more preferably 88% or more and 99% or less, and even more preferably 89% or more and 97% or less.
[0099] <Light Emitting Device>
[0100] Figure 1 is a schematic cross-sectional view illustrating the structure of a light-emitting device.
[0101] As shown in FIG. 1, the light-emitting device (100) comprises a light-emitting element (120), a heat sink (130), a case (140), a first lead frame (150), a second lead frame (160), a bonding wire (170), a bonding wire (172), and a composite (40).
[0102] The light-emitting element (120) is mounted on a predetermined area of the upper surface of the heat sink (130). By mounting the light-emitting element (120) on the heat sink (130), the heat dissipation of the light-emitting element (120) can be increased. Additionally, a substrate for a package may be used instead of the heat sink (130).
[0103] The light-emitting element (120) is a semiconductor device that emits excitation light. As the light-emitting element (120), for example, an LED chip that emits light with a wavelength of 300 nm or more and 500 nm or less, corresponding to near-ultraviolet to blue light, can be used. One electrode (not shown) disposed on the upper surface side of the light-emitting element (120) is connected to the surface of the first lead frame (150) through a bonding wire (170) such as a gold wire. In addition, the other electrode (not shown) formed on the upper surface of the light-emitting element (120) is connected to the surface of the second lead frame (160) through a bonding wire (172) such as a gold wire.
[0104] In the case (140), a roughly funnel-shaped concave portion is formed, in which the diameter of the hole gradually increases upward from the bottom surface. A light-emitting element (120) is provided on the bottom surface of the concave portion. The wall surface of the concave portion surrounding the light-emitting element (120) serves as a reflector.
[0105] The composite (40) is filled into the concave portion where the wall is formed by the case (140). The composite (40) is a wavelength conversion member that converts the wavelength of the excitation light emitted from the light-emitting element (120) into a long wavelength. As the composite (40), the composite of the present embodiment is used, and the phosphor (1) of the present embodiment is dispersed in a sealing material (30) such as resin. The light-emitting device (100) emits a mixed color of light from the light-emitting element (120) and light generated from the phosphor (1) that absorbs the light of the light-emitting element (120) and is excited. It is preferable that the light-emitting device (100) emits white light through the mixing of the light from the light-emitting element (120) and the light generated from the phosphor (1).
[0106] For reference, transparent resins such as silicone resin, epoxy resin, and uretain resin can be used as the sealing material (30) in the composite (40). The composite (40) can be manufactured by, for example, adding the α-type sialon phosphor of the present embodiment to a liquid resin or powdered glass or ceramics, mixing them uniformly, and then curing or sintering them by heat treatment.
[0107] In the light-emitting device (100) of the present embodiment, the change in light-emitting characteristics at high temperatures is suppressed by using the α-type sialon phosphor described above as phosphor 1. Therefore, the light-emitting device (100) is suitable for use in vehicles. However, to clarify for the sake of clarity, the use of the light-emitting device (100) is not limited to vehicle use. The light-emitting device (100) can also be applied to lighting applications, display device applications, etc., which are not vehicle applications.
[0108] For reference, in FIG. 1, a surface-mount type light-emitting device is exemplified, but the light-emitting device is not limited to a surface-mount type and may be a projectile type, COB (chip on board) type, or CSP (chip scale package) type.
[0109] Method for manufacturing α-type sialon phosphors
[0110] The method for manufacturing an α-type sialon phosphor of the present embodiment is,
[0111] A calcination process for obtaining a massive α-type sialon phosphor containing Eu elements by calcination, and
[0112] A grinding process for grinding the above-mentioned bulk α-type sialon phosphor to obtain a powdered α-type sialon phosphor, and
[0113] An N2 annealing process for annealing the powdered α-type sialon phosphor under a nitrogen gas atmosphere, in a temperature range of 1200°C to 1700°C and a time range of 5 hours to 30 hours, and
[0114] An H2 annealing process for annealing the powdered α-type sialon phosphor under a hydrogen gas atmosphere, in a temperature range of 1200°C or higher and 1700°C or lower and a time range of 5 hours or higher and 30 hours or lower, and
[0115] It includes an acid treatment process in which acid treatment is performed using an acidic aqueous solution on the powdered α-type sialon phosphor after the H2 annealing process.
[0116] In the method for manufacturing an α-type sialon phosphor of the present embodiment, preferably, the H2 annealing process is performed after the N2 annealing process.
[0117] In addition, it is preferable to perform a water effleurization process to classify the powdered α-type sialon phosphor after the above acid treatment process by water effleurization.
[0118] By the above manufacturing method, an α-type sialon phosphor with particularly few crystal defects can be obtained. Although the details are unclear, it is presumed that a combination of the N2 annealing process and the H2 annealing process is effective in reducing crystal defects.
[0119] The following describes each process.
[0120] · Sintering process
[0121] The calcination process can be carried out by referring to the conventional method for manufacturing α-type sialon phosphors. To briefly explain an example, (i) first, raw materials containing elements constituting an α-type sialon phosphor containing Eu (such as nitrides or oxides of each element) are mixed to obtain a mixture, and (ii) the mixture is filled into a boron nitride container and calcined in a nitrogen atmosphere at a temperature of 1650°C or higher and 1950°C or lower to obtain a bulk α-type sialon phosphor containing Eu elements.
[0122] Regarding the firing process, reference may be made to the descriptions in paragraphs 0036 through 0044 of International Publication No. 2020 / 203483 and the descriptions in the examples. In addition, reference may be made to the descriptions in other known literature.
[0123] · Grinding process
[0124] In the calcination process, an α-type sialon phosphor with an ingot-like shape is typically produced. By crushing this ingot-like α-type sialon phosphor using a crusher, mortar and pestle grinder, ball mill, vibratory mill, jet mill, etc., a powdered α-type sialon phosphor can be obtained.
[0125] By adjusting the degree of grinding, the particle size distribution, such as the median diameter of the α-type sialon phosphor, can be adjusted.
[0126] In addition to the grinding process, a sieving process may be performed. By performing the sieving process, the particle size distribution, such as median diameter, can be adjusted more precisely.
[0127] In addition, a process may be performed in which a crushed powdered α-type sialon phosphor is dispersed in an aqueous solution and left to stand for a certain period of time to remove particles that are difficult to settle due to their small particle size. By doing so, the particle size distribution, such as the median diameter, can be adjusted more precisely.
[0128] · N2 annealing process
[0129] The temperature of the N2 annealing process may be 1200°C or higher and 1700°C or lower, but preferably 1300°C or higher and 1600°C or lower.
[0130] The time for the N2 annealing process is 5 hours or more and 30 hours or less, but preferably 8 hours or more and 25 hours or less.
[0131] The pressure in the N2 annealing process is not particularly limited, but for example, it is 0.02 MPa·G or more and 0.9 MPa·G or less, preferably 0.02 MPa·G or more and 0.2 MPa·G or less.
[0132] The N2 annealing process may be carried out in a mixed gas atmosphere of N2 and an inert gas other than N2 (such as a noble gas), but preferably, it is carried out in a gas atmosphere consisting substantially only of N2. Furthermore, even in a mixed gas atmosphere, it is preferable that the proportion of N2 in the mixed gas be greater than 50 volume%, and more preferable that it be greater than 75 volume%. By doing so, it is believed that crystal defects in the α-type sialon phosphor are further reduced.
[0133] · H2 annealing process
[0134] The temperature of the H2 annealing process may be 1200°C or higher and 1700°C or lower, but preferably 1300°C or higher and 1600°C or lower.
[0135] The time for the H2 annealing process may be 5 hours or more and 30 hours or less, but preferably 8 hours or more and 25 hours or less.
[0136] The pressure in the H2 annealing process is not particularly limited, but for example, it is 0.02 MPa or more and 0.9 MPa or less, preferably 0.02 MPa or more and 0.1 MPa or less.
[0137] The H2 annealing process may be carried out in a mixed gas atmosphere of H2 and an inert gas other than H2 (such as a return gas), but preferably, it is carried out in a gas atmosphere consisting substantially only of H2. Furthermore, even when carried out in a mixed gas atmosphere, it is preferable that the proportion of H2 in the mixed gas be greater than 50 volume%, and more preferable that it be greater than 75 volume%. By doing so, it is believed that crystal defects in the α-type sialon phosphor are further reduced.
[0138] · Acid treatment process
[0139] In the acid treatment process, for example, a powdered α-type sialon phosphor is placed in an acidic aqueous solution and stirred using a stirrer.
[0140] Examples of acidic aqueous solutions include an acidic aqueous solution containing one acid selected from acids such as hydrofluoric acid, nitric acid, and hydrochloric acid, or a mixed acid aqueous solution obtained by mixing two or more of the above acids. Among these, an aqueous solution of hydrofluoric acid containing hydrofluoric acid alone and a mixed acid aqueous solution obtained by mixing hydrofluoric acid and nitric acid are more preferred. The concentration of the acidic aqueous solution stock solution is appropriately set according to the strength of the acid used, but is preferably 0.7% or more and 100% or less, and more preferably 0.7% or more and 40% or less. In addition, the temperature at which the acid treatment is performed is preferably 60°C or more and 90°C or less, and the reaction time (immersion time) is preferably 15 minutes or more and 80 minutes or less.
[0141] By performing high-speed stirring, sufficient acid treatment of the particle surface is facilitated. Here, "high speed" refers to the stirring device used; however, when using a laboratory-level magnetic stirrer, the stirring speed is, for example, 400 rpm or higher, and realistically, between 400 rpm and 500 rpm. From the perspective of the purpose of normal stirring, which is to constantly supply fresh acid to the particle surface, a stirring speed of about 200 rpm is sufficient; however, by performing high-speed stirring of 400 rpm or higher, sufficient treatment of the particle surface is facilitated through physical action in addition to chemical action.
[0142] By selecting appropriate stirring conditions, foreign substances or abnormalities (which can cause a decrease in luminescence characteristics) on the surface of the phosphor are sufficiently removed. As a result, it is believed that crystal defects in the entire α-type sialon phosphor are further reduced. As a result, it is believed that changes in luminescence characteristics under high-temperature environments can be made even smaller.
[0143] · Classification process
[0144] Any classification treatment may be performed to adjust the particle size distribution of the α-type sialon phosphor. Classification may be performed under dry or wet conditions. Classification may also be performed using various devices used industrially, such as sedimentation tanks, hydrocyclones, centrifuges, cyclones, and air separators. Among these, hydraulic classification using a sedimentation tank is preferred, but of course, the specific method of classification is not limited to hydraulic classification using a sedimentation tank.
[0145] Although embodiments of the present invention have been described above, these are examples of the present invention, and various configurations other than those described above may be adopted. Furthermore, the present invention is not limited to the embodiments described above, and modifications and improvements within the scope of achieving the objectives of the present invention are included in the present invention.
[0146] Examples
[0147] Embodiments of the present invention are described in detail based on examples and comparative examples. For the sake of clarity, the present invention is not limited to the examples.
[0148] <Preparation of α-type sialon phosphors>
[0149] (Examples 1, 2 and Comparative Example 1)
[0150] An α-type sialon phosphor was prepared by the following procedure.
[0151] (1) Sintering process
[0152] Inside a glove box, as a composition of raw material powders, silicon nitride powder (manufactured by Ube Kosan Co., Ltd., E10 grade) was 62.4 parts by mass, aluminum nitride powder (manufactured by Tokuyama Corporation, E grade) was 22.5 parts by mass, europium oxide powder (manufactured by Shin-Etsu Kagaku Kogyo Co., Ltd., RU grade) was 2.2 parts by mass, and calcium nitride powder (manufactured by Kojundo Kagaku Genkyusho Co., Ltd.) was 12.9 parts by mass, and after dry blending the raw material powders, a raw material mixed powder was obtained by passing them through a nylon sieve with a mesh size of 250 μm. 120 g of the raw material mixed powder was filled into a lidded cylindrical boron nitride container (manufactured by Denka Co., Ltd., N-1 grade) with an internal volume of 0.4 liters.
[0153] The raw material mixture powder in its container was subjected to heat treatment (calcination) at 1800°C for 16 hours in an electric furnace of a carbon heater under an atmospheric pressure nitrogen atmosphere. Since the calcium nitride contained in the raw material mixture powder is prone to easy hydrolysis in air, the boron nitride container filled with the raw material mixture powder was removed from the glove box, quickly set up in the electric furnace, and immediately vacuum-evacuated to prevent the reaction of calcium nitride.
[0154] (2) Grinding process
[0155] The sintered product obtained in (1) above was appropriately crushed or broken down using a mortar and pestle, and passed through a sieve with a mesh size of 150 μm to obtain phosphor powder. When the crystal phase of this phosphor powder was investigated by X-ray diffraction using CuKα rays, the crystal phase present was found to be α-type sialon.
[0156] (3) N2 annealing process
[0157] The powdered α-type sialon phosphor obtained from the grinding process of (2) above was placed in a boron nitride container and covered. This container was placed in a heating furnace and heat treatment was performed under a nitrogen gas atmosphere under the conditions described in the "N2 annealing" column of Table 1 below. After cooling, the orange powder recovered from the container was sieved with a mesh size of 75 μm. Thus, N2 annealed phosphor powder was obtained.
[0158] (4) H2 annealing process
[0159] The N2-annealed phosphor powder of (3) above was placed in a boron nitride container and covered. This container was placed in a furnace and heated under a hydrogen gas atmosphere. The heating conditions were set to the conditions described in the "H2 annealing" column of Table 1 below. After cooling, the orange powder recovered from the container was sieved through a mesh size of 75 μm. This obtained the H2-annealed phosphor powder.
[0160] (5) Acid treatment process
[0161] First, a stock solution was prepared by mixing 50 mL of 50% hydrofluoric acid and 50 mL of 70% nitric acid. 300 mL of distilled water was added to this stock solution, and the concentration of the stock solution was diluted to 25% to prepare 400 mL of a mixed acid aqueous solution.
[0162] 30g of phosphor powder recovered after the H2 annealing process of (4) was added to this mixed acid aqueous solution, and the temperature of the mixed acid aqueous solution was maintained at 80℃ and stirred for 60 minutes at a rotation speed of 450rpm using a magnetic stirrer.
[0163] After stirring was finished, the acid attached to the phosphor was thoroughly washed off with distilled water. The washed phosphor powder was recovered by filtration and dried.
[0164] The particle size distribution of the phosphor powder after drying was measured using a Microtrac MT3300EX II (Microtrac Bell Co., Ltd.) by the laser diffraction scattering method in accordance with JIS R1629:1997.
[0165] Specifically, first, 0.5 g of powdered α-type sialon phosphor was added to 100 cc of ion-exchanged water, and a dispersion treatment was performed for 3 minutes using an Ultrasonic Homogenizer US-150E (Nippon Seiki Seisakusho Co., Ltd., chip size φ20 mm, amplitude 100%, oscillation frequency 19.5 KHz, amplitude approx. 31 μm) to obtain a dispersion. This dispersion was set up in an MT3300EX II, and the particle size distribution was measured.
[0166] From the obtained particle size distribution, the median diameter D 50 saved.
[0167] Conditions for the N2 annealing process and the H2 annealing process, and D 50 It is shown in Table 1.
[0168] [Table 1]
[0169]
[0170] Electron Spin Resonance Measurement
[0171] For the α-type sialon phosphors of Examples 1 and 2 and Comparative Example 1, electron spin resonance measurements were performed as follows. Then, the crystal defect density of the α-type sialon phosphor at 25°C, 200°C, 300°C, and 600°C was determined as the spin density value of the signal near g=2.
[0172] (Measurement Procedure)
[0173] Sample powder (about 60 mg) was placed in an ESR sample tube and set up in the device, and simulated air (flow rate: 20 mL min-1) was circulated through the sample tube, and an ESR measurement of g=2 was performed at room temperature (25℃).
[0174] After that, the temperature was raised to 200℃ at a heating rate of 30℃ / min, maintained for 30 min, and then ESR measurements were performed at g=2.
[0175] In addition, afterwards, the temperature was raised to 300℃ at a heating rate of 30℃ / min, maintained for 30 min, and then ESR measurements were performed at g=2.
[0176] In addition, afterwards, the temperature was raised to 600℃ at a heating rate of 30℃ / min, maintained for 30 min, and then ESR measurements were performed at g=2.
[0177] (Measuring device and measurement conditions)
[0178] The BRUKER ESR device "EMXplus" and the BRUKER high-temperature cavity "ER4114HT" were used. In addition, the measurement conditions were as follows.
[0179] Magnetic field scan range: around 3350–3550G
[0180] Modulation: 100kHz, 5G
[0181] Microwave: 9.67 GHz, 1 mW
[0182] Scan time: 80s × 4 times
[0183] Time constant: 327.68ms
[0184] Number of data points: 1000 points
[0185] (Interpretation of measurement data)
[0186] The ESR spectrum is typically observed as a first-order derivative curve to sensitively observe the irregularities of the absorption spectrum of electromagnetic waves. Since the absorption intensity is proportional to the spin number, the ESR spectrum is integrated twice to convert the derivative curve into an integral curve, and the spin number of the sample is quantified from the peak area ratio with that of a standard sample.
[0187] Regarding the integration range, the line passing through g=2.0171 and g=1.9838 in the first derivative curve was subtracted as the baseline, and the range from g=2.0171 to 1.9838 was integrated. In this way, the peak area of the sample originating from g=2 was obtained.
[0188] For the analysis, BRUKER’s ESR software “WinEPR” was used.
[0189] (Calculation of spin number and spin density)
[0190] The number of spins of the sample at 25°C was determined by performing a separate ESR measurement on a secondary standard sample (ion-implanted polyethylene film) with a known number of spins and calculating the peak area ratio with that. Additionally, the number of spins of the sample per unit mass (spin density [spins / g]) at 25°C was calculated by dividing the number of spins of the sample by the mass of the sample provided for measurement [g].
[0191] For reference, the spin number of the second standard sample (ion-implanted polyethylene film) was determined by performing a separate ESR measurement at 25°C on the first standard sample (copper sulfate pentahydrate) with a known spin number and using the peak area ratio with that.
[0192] The number of spins of the sample at 200°C was obtained from the peak area ratio with the secondary standard sample (ion-implanted polyethylene film) in the same way as at 25°C, and then corrected for the effect of the measurement temperature on the signal intensity by multiplying the measurement temperature ((273+200)[K]) ÷ room temperature ((273+25)[K]) (Curie's Law). In addition, the number of spins of the sample per unit mass (spin density [spins / g]) at 200°C was obtained by dividing the number of spins of the sample by the mass of the sample provided for measurement [g].
[0193] Likewise, the spin density [spins / g] of the sample at 300℃ was calculated. For reference, when performing temperature correction according to Curie's law, the measured temperature ((273+300)[K]) ÷ room temperature ((273+25)[K]) was multiplied.
[0194] Likewise, the spin density [spins / g] of the sample at 600℃ was calculated. For reference, when performing temperature correction according to Curie's law, the measured temperature ((273+600)[K]) ÷ room temperature ((273+25)[K]) was multiplied.
[0195] (supplement)
[0196] The absorption intensity in the ESR spectrum varies depending on the measurement conditions. Therefore, the influence of the resonator Q value, receiver gain, number of integration cycles [cycles], modulation [G], conversion time [ms], microwave power [mW], sample tube inner diameter [mm], resonator center position [mm], insertion sample length [mm], and spin quantum number was appropriately corrected during analysis.
[0197] The results are shown in Table 2 below. The unit of the values is spins / g.
[0198] [Table 2]
[0199]
[0200] <Evaluation: Change in luminescence characteristics due to temperature>
[0201] For each α-type sialon phosphor of the example and comparative example, the absorption rate, internal quantum efficiency, external quantum efficiency, and their temperature dependence were obtained by using a spectrophotometer (QE-2100 manufactured by Otsuka Denshi Co., Ltd.) to subtract the re-excited fluorescence from the total fluorescence and performing a re-excitation method correction.
[0202] The above absorption rate, internal quantum efficiency, and external quantum efficiency were obtained by changing the sample temperature from room temperature to 300°C, and the temperature change of the internal quantum efficiency and external quantum efficiency was evaluated.
[0203] As a quantitative indicator of temperature change, the "internal quantum efficiency retention rate" at each temperature relative to the value of internal quantum efficiency at room temperature, and the "external quantum efficiency retention rate" at each temperature relative to the value of external quantum efficiency at room temperature were calculated.
[0204] The above evaluation results are summarized and shown in Tables 3, 4, and 5.
[0205] [Table 3]
[0206]
[0207] [Table 4]
[0208]
[0209] [Table 5]
[0210]
[0211] As can be understood from the table above, the density of crystal defects at 25°C or 200°C is 1.0×10 15 In Comparative Example 1, which is greater than spins / g, the decrease in internal quantum efficiency and external quantum efficiency was significant, especially at a high temperature of 300°C.
[0212] Meanwhile, the density of crystal defects at 25℃ or 200℃ is 1.0×10 15In Examples 1 and 2, which have spins / g or less, the decrease in internal quantum efficiency and external quantum efficiency was suppressed even at high temperatures. That is, the change in luminescence characteristics was small even at high temperatures. The phosphors of Examples 1 and 2 can be said to be desirable for application in automotive applications.
[0213] This application claims priority based on Japanese Patent Application No. 2023-058890 filed on March 31, 2023, and incorporates all of the disclosures thereof herein. Explanation of the symbols
[0214] 1 Phosphor 30 bag materials 40 complex 100 light-emitting devices 120 light-emitting elements 130 heat sink 140 cases 150 1st Lead Frame 160 2nd Lead Frame 170 bonding wire 172 Bonding Wire
Claims
Claim 1 As an α-type sialon phosphor containing the element Eu, the density of crystal defects in the α-type sialon phosphor is 1.0 × 10⁻⁶, as the value of the spin density of the signal near g=2 detected by electron spin resonance measurement at 25°C. 15 spins / g or less, and composition, general formula: (M1 x , M2 y , Eu z )(Si 12-(m+n) Al m+n )(O n N 16-n It is represented as ), and in the above general formula, M1 is a monovalent Li element, M2 is Ca, 0≤x<2.0, 0≤y<2.0, 0 <z≤0.5, 0<x+y, 0.3≤x+y+z≤2.0, 0<m≤4.0, 0<n≤3.0인 α형 사이알론 형광체. Claim 2 As an α-type sialon phosphor containing the element Eu, the density of crystal defects in the α-type sialon phosphor is 1.0 × 10⁻⁶, as the value of the spin density of the signal near g=2 detected by electron spin resonance measurement at 200°C. 15 spins / g or less, and composition, general formula: (M1 x , M2 y , Eu z )(Si 12-(m+n) Al m+n )(O n N 16-n It is represented as ), and in the above general formula, M1 is a monovalent Li element, M2 is Ca, 0≤x<2.0, 0≤y<2.0, 0 <z≤0.5, 0<x+y, 0.3≤x+y+z≤2.0, 0<m≤4.0, 0<n≤3.0인 α형 사이알론 형광체. Claim 3 As an α-type sialon phosphor described in claim 2, the density of crystal defects in the α-type sialon phosphor is, at 25°C, 1.0 × 10⁻⁶ as the value of the spin density of the signal near g=2 detected by electron spin resonance measurement. 15 α-type sialon phosphor with spins / g or less. Claim 4 As an α-type sialon phosphor described in any one of claims 1 to 3, the density of crystal defects in the α-type sialon phosphor is, at 300°C, 1.0 × 10⁻⁶ as the value of the spin density of the signal near g=2 detected by electron spin resonance measurement. 15 α-type sialon phosphor with spins / g or less. Claim 5 As an α-type sialon phosphor described in any one of claims 1 to 3, the density of crystal defects in the α-type sialon phosphor is 9.5×10⁻⁶ as the value of the spin density of the signal near g=2 detected by electron spin resonance measurement at 600°C. 15 α-type sialon phosphor with spins / g or less. Claim 6 An α-type sialon phosphor as described in any one of claims 1 to 3, wherein the internal quantum efficiency at 200°C is 87% or higher. Claim 7 An α-type sialon phosphor as described in any one of claims 1 to 3, wherein the internal quantum efficiency at 300°C is 80% or more. Claim 8 An α-type sialon phosphor as described in any one of claims 1 to 3, wherein the internal quantum efficiency retention rate represented by {(internal quantum efficiency at 24°C) / (internal quantum efficiency at 300°C)} × 100[%] is 89% or higher. Claim 9 An α-type sialon phosphor as described in any one of claims 1 to 3, wherein the external quantum efficiency retention rate represented by {(external quantum efficiency at 24°C) / (external quantum efficiency at 300°C)} × 100[%] is 88% or higher. Claim 10 A light-emitting device comprising a light-emitting element and an α-type sialon phosphor described in any one of claims 1 to 3, and a wavelength conversion unit that converts light emitted from the light-emitting element into a long wavelength. Claim 11 A method for manufacturing an α-type sialon phosphor, comprising: a calcination process for obtaining a bulk α-type sialon phosphor containing Eu elements by calcination; a grinding process for grinding the bulk α-type sialon phosphor to obtain a powder α-type sialon phosphor; an N2 annealing process for annealing the powder α-type sialon phosphor under a nitrogen gas atmosphere at a temperature range of 1200°C to 1700°C and a time range of 5 hours to 30 hours; an H2 annealing process for annealing the powder α-type sialon phosphor under a hydrogen gas atmosphere at a temperature range of 1200°C to 1700°C and a time range of 5 hours to 30 hours; and an acid treatment process for performing acid treatment on the powder α-type sialon phosphor using an acidic aqueous solution after the H2 annealing process. Claim 12 delete
Citation Information
Patent Citations
Process for producing fluorescent substance and fluorescent substance produced thereby
WO2011024296A1
Phosphor, production method thereof, and light emitting device
JP2015224339A
Process for producing fluorescent substance and fluorescent substance produced thereby
US20120037849A1